Understanding and Management of Neurobehavioral Difficulties in Patients with Duchenne Muscular Dystrophy: PhD thesis presented on 24-06-2024 at KU Leuven, Leuven, Belgium - Geuens, Sam; De Waele, Liesbeth; Lemiere, Jurgen; Doorenweerd, Nathalie; Goemans, Nathalie (Belgian Journal of Paediatrics, 2024)
Patients with Duchenne muscular dystrophy (DMD) face an increased risk to develop neurobehavioral problems linked to brain dystrophin deficiency. This PhD thesis explores the impact of corticosteroid treatment and genotype on brain morphology and their correlations with neurobehavioral outcomes. Using MRI, significant differences in gray matter volumes, subcortical volumes, and brain morphology were found between DMD patients treated daily with corticosteroids and those treated intermittently. Additionally, differences were observed based on genotypes. A new term, Duchenne Muscular Dystrophy-Associated Neurobehavioral Difficulties (DuMAND), and the DuMAND Checklist were introduced for systematic screening of neurobehavioral difficulties in DMD. Finally, clinical experiences with psychopharmaceuticals to treat severe neurobehavioral difficulties in DMD patients were investigated.